Family meeting or Care Planning Meeting? : a Multidisciplinary Team action research study in a hospital setting - Donnelly, Sarah (Trinity College (Dublin, Ireland). School of Social Work and Social Policy, 2012)
Care Planning Meetings (CPM's) are regularly conducted in hospital settings where patient, family members and the MDT meet to exchange information, plan for the future and facilitate decision-making. In the Age Related Healthcare Unit where this research took place, CPM's were being used more frequently to determine care plans for older people, without any particular protocol for these meetings, or consistency about the participation of the patient at the centre of the care planning process.
Keywords: Social Studies, Ph.D.; Ph.D. Trinity College Dublin